Hubungan Tingkat Pengetahuan Siswi Kelas 10 Terhadap Kepatuhan Vulva Hygiene Saat Menstruasi - Sri Kanti; Maulida Nurfazriah Oktaviana; Sumarman Sumarman (Jurnal Ilmiah Kesehatan Rustida, 2021)
Vulva hygiene during menstruation is a problem that is considered taboo to be dis- cussed so that the obligation to maintain vaginal health is often neglected. The in- cidence of ISR in Indonesia reaches 90-100 cases per 100,000 population per year. Cases in East Java as much as 77% occurred in adolescent girls. A preliminary study in one of the vocational high schools in Glenmore District as many as 30 female students experienced vaginal discharge and itching in the female area. The purpose of the study was to determine the relationship between the level of knowledge of 10th grade students on vulva hygiene adherence during menstruation at the Glenmore District Vocational High School. This type of research uses quantitative analysis with a cross sectional design. The population is 75 students and a sample of 35 students who fill out the questionnaire. Using simple random sampling tech- nique. The research instrument used a questionnaire. The results of this study were obtained from 35 respondents who filled out the questionnaire as many as 13 stu- dents with sufficient knowledge (37.1%) and 16 students who were not obedient in performing vulva hygiene during menstruation (45.7%). Based on the results of the chi square test, p value 0.277 > = 0.05, which means that there is no relationship between the level of knowledge of grade 10 students on vulvar hygiene compliance during menstruation. It is expected that respondents will increase their knowledge about vulvar hygiene during menstruation.